Statistics - Witte, Robert S. 4 0 16; Witte, John S.; 5 (Hoboken, N.J. : Jhon Wiley & Sons, 2010)
The authors of this highly accessible book provide business professionals with a clear and methodical approach to essential statistical procedures. --from publisher description.
Describing data with tables and graphs -- Describing data with averages -- Describing variability -- Normal distributions and standard (z) scores -- Describing relationships : correlation -- Regression -- Populations, samples, and probability -- Populations and samples -- Probability -- Sampling distribution of the mean -- Introduction to hypothesis testing : the z test -- More about hypothesis testing -- Estimation (confidence intervals) -- t Test for one sample -- t Test for two independent samples -- t Test for two related samples (repeated measures) -- Analysis of variance (one factor) -- Analysis of variance (repeated measures) -- Analysis of variance (two factors) -- Chi-square (Xp2s) test for qualitative (nominal) data -- Tests for ranked (ordinal) data -- Postscript : which test? -- Appendices. Math review ; Answers to selected questions ; Tables ; Glossary.
Includes index.
Keywords: 2 -- 0; 6; Statistics. -- 20; 20; 2